Use of Red Cell Indices for Screening of Hereditary Spherocytosis in Neonates: A Report of Two Cases Confirmed by Exome Sequencing - Vinay Batthula; Laxman Basany; Vaidehi Reddy Chappidi; Gandrakota Naga Priyanka; Abid Ali (Journal of Clinical and Diagnostic Research, 2023)
Prolonged unconjugated hyperbilirubinaemia is defined as neonatal jaundice persisting beyond 14 days of life. Hereditary Spherocytosis (HS) often remains underdiagnosed and is a notable cause of prolonged neonatal jaundice. Coombs negative haemolytic anaemias are an important cause of unconjugated hyperbilirubinaemia, and HS is one of the most common inherited red cell membrane disorders. Other causes of prolonged unconjugated jaundice include extravasated blood (cephalhaematoma, bruises, intraventricular haemorrhage in preterm infants), haemolysis (blood group incompatibility, red blood cell enzymopathies, and membranopathies), urinary tract infection, congenital hypothyroidism, and rare familial disorders such as Gilbert’s syndrome and Crigler-Najjar syndromes I and II. Herein, the authors present a case report of two male neonates (three week-old and 25dayold) who presented with hyperbilirubinaemia requiring intensive phototherapy, blood transfusion, an exchange transfusion, and were diagnosed with HS. A significant family history suggested haemolytic anaemia, and red cell indices, namely Mean Corpuscular Haemoglobin Concentration (MCHC), Mean Corpuscular Volume (MCV), and the ratio of MCHC/MCV (neonatal HS index), helped suspect HS. Whole exome sequencing identified the specific mutation and confirmed the diagnosis of HS. Both of these neonates presented with prolonged neonatal jaundice, and HS was suspected based on the family history and red cell indices, namely MCHC and MCHC/MCV ratio, as highlighted in the present case series.